Recidiva de peso e comportamento alimentar em mulheres fisicamente ativas e inativas após 24 meses de cirurgia bariátrica - RODRIGUES, Letícia dos Santos (2023)
Introduction: In cases of severe obesity bariatric surgery has been indicated to promote weight loss and control of comorbidities. However, after two years of surgery, weight regain is common, which is related to physical inactivity and behavioral components. Thus, it is imperative to know these factors to ensure good results and to direct the best nutritional treatment. Aim: To test the association between the anthropometric profile and the eating behavior with the practice of physical activity in patients after 24 months of bariatric surgery. Methodology: This is a crosssectional study of 44 female patients, aged between 18 and 59 years, who underwent Gastric Bypass or Sleeve for more than 24 months. Sociodemographic, anthropometric characteristics, food behavior and physical activity were collected. All patients signed the Term of Free and Informed Consent and this research was approved by the Ethics and Research Committee (no. 2,170,863). For statistical analysis, the Kolmogorov-Smirnov tests were used; Spearman; Friedman and Mann- Whitney. The data were analyzed in SPSS software v.21. The data were analyzed in SPSS software v.21. Results: The mean excess weight loss was satisfactory (> 50%), but the mean weight regain 16.4 ± 11.2%, and the weight loss (kg) was statistically lower in the physically active group (p= 0.049). There was a predominance of emotional feeding in both groups (active p 0.025, inactive p=0.040). There was a significant inverse correlation (p = 0.045; r² = 0.259) between dietary restriction behavior and weight regain (%) and the time of practice of physical activity (min) presented a statistically significant inverse correlation with (r2=272; p=0.042) with weight regain (%). Conclusion: It was possible to observe a lower weight regain in physically active patients, and a predominance of the emotional eating domain, evidencing the need to model food behavior and to encourage the practice of physical exercises in these patients.